Le Maghreb et l’Europe face à la crise du Sahel : Coopération ou rivalités ? - Aomar Baghzouz (L’Année du Maghreb)
This paper proposes an evaluation of the recent crises in the Sahel and it repercussions for cooperation between Europe and the Maghreb and among the countries of the Maghreb. The central argument of the study is that the Sahel should be included in economic and security policy discussions between the Maghreb and Europe. While seeking to identify strategies used by different international actors involved in the Sahel, whether states or relevant regional organizations (, EU, UMA…), the article focuses on the cooperative actions and rivalries which led to the regional crisis. In view of the geopolitical reconfigurations affecting the entire region, the article concludes with the need to revive existing cooperation frameworks, and at the same time, to work for a more effective Maghreb-Europe-Sahel cooperation in confronting emerging transnational challenges.